501 must be there events - Beare, Emma (London : Bounty Books, 2014)
This fantastic book enables you to travel the world from the comfort of your armchair, meet new people, enjoy sporting events and unusual festivities in foreign lands and deepen your knowledge of other cultures and religions. There is a wide selection of festivals and events, from kite festivals in China to beer festivals in Germany, from film to fashion, from bull fighting to camel wrestling, from carving chocolate in Italy to carving ice in Central Asia. This title is ideal for personal use to plan your trips to coincide with particular events, or it would make an excellent gift.
North America -- Central America & the Caribbean -- South America -- Africa -- Europe -- Eastern Mediterranean & Middle East -- Asia -- Australasia & Oceania.
Includes index.
Keywords: TRAVEL GUIDEBOOKS; SPECIAL EVENTS -- GUIDEBOOKS